Maternal protein restriction combined with postnatal sugar consumption alters liver proteomic profile and metabolic pathways in adult male offspring rats - Ribeiro, Isabelle Tenori [UNESP]; Fioretto, Matheus Naia [UNESP]; dos Santos, Sérgio Alexandre Alcantara [UNESP]; Colombelli, Ketlin Thassiani [UNESP]; Portela, Luiz Marcos Frediani [UNESP]; Niz Alvarez, Marcus Vinicius [UNESP]; de Magalhães Padilha, Pedro [UNESP]; Delgado, Aislan Quintiliano [UNESP]; Marques, Marcus Vinicius Lage Silva Giaculi [UNESP]; Bosqueiro, José Roberto [UNESP]; Seiva, Fábio Rodrigues Ferreira [UNESP]; Barbisan, Luís Fernando [UNESP]; et al. (Elsevier, 2024)
This study investigated the impact of maternal protein restriction (MPR) and early postnatal sugar consumption (SUG) on the liver health of adult male descendant rats. Male offspring of mothers fed a normal protein diet (NPD) or a low protein diet (LPD) were divided into four groups: Control (CTR), Sugar Control (CTR + SUG), LPD during gestation and lactation (GLLP), and LPD with sugar (GLLP + SUG). Sugar consumption (10% glucose diluted in water) began after weaning on day 21 (PND 21), and at 90 days (PND 90), rats were sacrificed for analysis. Sugar intake reduced food intake and increased water consumption in CTR + SUG and GLLP + SUG compared to CTR and GLLP. GLLP and GLLP + SUG groups showed lower body weight and total and retroperitoneal fat compared to CTR and CTR + SUG. CTR + SUG and GLLP + SUG groups exhibited hepatocyte vacuolization associated with increased hepatic glycogen content compared to CTR and GLLP. Hepatic catalase activity increased in GLLP compared to CTR. Proteomic analysis identified 223 differentially expressed proteins (DEPs) among experimental groups. While in the GLLP group, the DEPs enriched molecular pathways related to cellular stress, glycogen metabolic pathways were enriched in the GLLP + SUG and CTR + SUG groups. The association of sugar consumption amplifies the effects of MPR, deregulating molecular mechanisms related to metabolism and the antioxidant system.
Keywords: Liver; Maternal protein restriction; Metabolism; Proteomic; Sugar consumption